African christianity and the modern challenges of ecumenism: the Nigerian context (2019)
The engagement of the founding fathers of ecumenism in bringing church leaders to the realisation of the need for collaboration towards the achievement of unity especially among Christians in Nigeria is laudable. Even evidences abound that in recent times those who had shown apathy to ecumenical activities in Nigeria in the past are beginning to embrace the ideals it stands for with apparent commitment. However, in contemporary times, some attitudes and practices which nearly frustrated the efforts of ecumenism at inception are rearing their heads again; and this is inimical to the unity of churches in Africa. This paper, therefore, attempts an investigation into such attitudes and practices with a view to ascertaining their effects on the unity of the church and making useful recommendations for the promotion of ecumenism in Nigeria